EDUCATIONAL PARALLEL COMPUTING SYSTEM: BUILDING CAPABILITIES AND CONFIGURATION OPTIONS (Modern information system and technologies, 2018)
Because it`s very important to have a really educational parallel computer system for study architecture and programming techniques of computer system, which have a few process and Distributed Shared Memory. For example, the efficiency of this systems can be low. Possibilities of building educational cluster  investigate in the work, based on the available Hardware and Software, in order to justify choice of the best solution, by the measure of efficiency/ cost of a computer system. Keywords: cluster system, supercomputer, compute node, parallel programming.